Evaluation of cytotoxic and free radical scavenging activities of cinnamomum zeylanicum bark extracts - Bhandari, Maitri (My University, 2015)
Traditional/Herbal medicines are plant derived products which include crude plant extracts such as fruit, flower, bark, materials which are native to an area. These constitute a major part of Complementary and Alternative Medicines (CAMs) which are being researched thoroughly due to their lower risks of side effects. Cancer is a disease of uncontrolled cell growth and proliferation and the treatments available like Chemotherapy also cause non-specific cytotoxicity to normal cells. Several phytochemicals present in spices have shown a potential to treat cancer. Cinnamomum zeylanicum is a commonly used spice with many medicinal properties but not much scientific data is available on its cytotoxic effects. Hence, the present study focuses on evaluation of the cytotoxic effects of Cinnamomum zeylanicum bark extracts (Hexane, Dichloromethane, Chloroform and Methanol) on Cancer cell lines HeLa and RAW 264.7 and their free radical scavenging activity. Phenol content was found to be highest in methanol extract. All extracts showed cytotoxic effects but more pronounced effects were seen in the case of hexane followed by DCM for both cell lines. Chloroform and DCM at some concentrations showed proliferative response in both cell lines. All extracts possessed free radical scavenging activity but the maximum was found in methanol extract. This could be attributed to the presence of high phenol content in this extract. Methanol also induced proliferation in case of stimulated PBMCs which may be due to the presence of some compounds. The experimental data thereby support the use of Cinnamomum zeylanicumin traditional medicines.
MT, DBT
Keywords: Herbal medicines; Cinnamomum zeylanicum; Cytotoxicity; Antioxidant; Phenolic content; DBT